Familiarity of emergency personnel towards emergency preparedness - Abdul Rahman, Ahmad Nu'man; Ahayalimudin, Nurul'Ain (2015)
Emergency preparedness is important, as it will reduce the impact after the disaster. Since Malaysia received less disaster, familiarity had become a gap as unfamiliar with disaster will cause incompetency in management, skills, knowledge and many more. Objective: To identify emergency healthcare personnel of four hospitals of northern region on the familiarity towards emergency preparedness. Methodology: A quantitative comparative cross-sectional study design. The data were collected from 192 emergency personnel by using Emergency Preparedness Information Questionnaire (EPIQ) based on inclusion and exclusion criteria. Results: The mean of familiarity of emergency personnel by hospitals are HTF= 2.72, HSB= 2.72, HPP= 2.42 and HRPB= 2.52. There is a significant association between age and familiarity for 3 hospitals as p˂0.05 with HSB (p=0.005), HPP (p=0.019) and HRPB (p=0.000). There is also a significant association between working experience and familiarity in HSB (p=0.002), HPP (p=0.044) and HRPB (p= 0.000) as p<0.05. Apart from that, there is a significant association between involvement in disaster response with familiarity in HSB (p=0.023), HPP (p= 0.013) and HRPB (p=0.003) as p<0.05. Besides, there is a significant association also between attended disaster-related education/training with familiarity in HTF (p=0.022), HSB (p= 0.000) and HRPB (p= 0.000) as p<0.05. Result revealed there is no significant difference among those 4 hospitals as p˃0.05. Conclusion: Results revealed that age, working experience, involvement in disaster response and involvement in disaster- related education/ training are significantly associated with familiarity. However, there is no significant difference between familiarity of emergency personnel in four hospitals. It was expected that more education and training will be conducted by the department, or even at states level in order to improve familiarity of emergency personnel on emergency preparedness.